Emphysematous epididymo-orchitis as a camouflage of prostate invasion secondary to rectum cancer: A case report. Issue 30 (July 2016) - Yen, Ching-Heng; Liu, Chin-Yu; Cha, Tai-Lung; Wu, Sheng-Tang; Meng, En; Sun, Guang-Huan; Yu, Dah-Shyong; Chen, Hong-I; Chang, Sun-Yran; Tsao, Chih-Wei
Abstract: Introduction: Emphysematous epididymo-orchitis is a rare cause of acute scrotum pain characterized by gas formation within the tissue. Diabetes mellitus and recto-seminal fistula secondary to sigmoid diverticulitis are generally accepted as being responsible for this disease. However, prostate invasion secondary to rectal cancer may be considered to be a newly identified pathogenetic mechanism. Herein, we report this rare case and illustrate the pathogenesis. Case presentation: A 69-year-old man arrived at our emergency department presenting with sepsis and acute scrotal pain. Emphysematous epididymo-orchitis was diagnosed by scrotal sonography initially; however, advanced rectal cancer with prostate invasion was diagnosed by CT after a recurrent episode. An exploratory laparotomy with abdominoperineal resection and radical prostectomy were performed after neoadjuvant chemoradiotherapy. Histopathologic analysis confirmed the previous diagnosis. Emphysematous epididymo-orchitis caused by advanced rectal cancer is very rare, and our case is the first to be reported according to a literature search. Neoadjuvant chemoradiotherapy plus extended surgery can achieve a good oncological outcome. Conclusion: This case indicated that the very rare presentation as emphysematous epididymo-orchitis caused by locally advanced colorectal cancer.